The second report from Turkey: waist percentiles for 6-11-year-old children in Elazig Province, Eastern Anatolia - Pirincci, Edibe; Cicek, Betul; Acik, Yasemin; Ozturk, Ahmet; Durmus, Birsen (Walter de Gruyter Gmbh, 2012)
Objective: To construct waist percentiles for 6-11-year-old Turkish children in Elazig Province, Eastern Anatolia. Methods: This cross-sectional study was performed with 3342 (1708 boys and 1634 girls) children from March to June 2007. Waist circumferences (WC) were measured between the lowest rib and the superior iliac crest, and centile curves were constructed with the Lambda-Mu-Sigma (LMS) method. Results: Towards 6-11 years, WC 50th percentile ranged from 57.54 to 67.04 cm in boys and 55.77 to 64.58 cm in girls. For both genders, WC increased with age. At each age, boys had higher WC values than girls. For the entire sample, mean WC was 62.5 +/- 6.8 cm for boys and 59.8 +/- 6.2 cm for girls. Median WC was 62.0 cm (32.0-90.0) for boys and 59.0 cm (46.0-87.0) for girls. Conclusions: The large differences in the values obtained worldwide emphasize the necessity of providing population-specific WC reference curves from different populations, which in turn may result in an international reference standard similar to that provided for body mass index.
Keywords: anthropometric indices; obesity; Turkish children; waist circumference